(3JGQjN GdeOjfI GdefhQIs - (3YeQ Hf THI (B((3hGSeg RjO(B) (3Hf YHjOI Hf QjWI GdfejQj GdHUQj, CHh RjO,J (B262 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg HcdGe Yf GdLfGFR hehGVYgG (B: (3HGH PcQ ebGe LHQjd Ydjg GdSdGe bGd CHh ZSGf (B: (3YdGeI ebGe LHQjd Ydjg GdSdGe GdPi jYQa HgG Gdjhe Cfc JNQL ef GdHGH GdPi jbGd dg HGH Bd YKeGf s
(3BNQgG (B:s
(3jfJgi GdehLhO efg Hbhd MSGf Hf KGHJ QVi Gddg Yfg (B: (3Ef JeS OGQ GHf YaGf NGhjI HGH UQjY hHGH eMQb VQH abO jUGOa HGZi GdNjQ MGLJg ajgG hjChi EdjgG GdLhO hGdMSH s
(3GdfSNI LRA ef GdeNWhWs
(3HgG fXGe GdJYbjHIs
(3cJH bGQF Ydi GdUaMI GdChdi Cf gPg GdbWYI ef JGQjN GHf THI HNW GdMGaX GdSNdGhi JdejP GHf MLQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B47 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B286s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs